Diary of a wimpy kid: THE THIRD WHEEL - Kinney, Jeff (Puffin London, 2009)
Allows you to draw your own Wimpy-Kid-style cartoons, fill in facts and lists, check out the full-colour comics inside and even write your own Wimpy Kid journal, just like Greg.